PENAMPAKAN DAN FENOMENOLOGI SEJARAH DALAM NOVEL HIKAYAT KADIROEN DAN STUDENT HIDJO (Historical Phenomena in Two Novel Hikayat Kadioroen and Student Hidjo) - Ahyar Anwar (Balai Bahasa Sulawesi Selatan, 2009)
This writing is a study about historical phenomena in two early novel which published in 1918 and 1920 in Indonesia. It use hermeneutic and genetic structuralism analysis to find actual relevance and historical exegesis in those two novels of Modern Indonesian Literature. It becomes the basic of fundament relation between literary and history also in historical respond context of Indonesia literature. Novel Hikayat Kadiroen and Student Hidjo are the part of Indonesia historical movement it self. Firstly, since the position of novel has been in accordance with the birth of national movement organisation at pre-liberation era in Indonesia. Secondly, since the author of Novel Hikayat Kadiroen, Semaoen and novel student Student Hidjo,Mas Marco Kartodikromo were activist of national movement at their era. Historically important aspect is controversial side of both of the novels in history of Indonesian literature caused by being considered as “left ideology” novel which were radical at that time.